1967
DOI: 10.1161/01.res.20.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and Chemical Studies of the Localization of Adrenergic and Cholinergic Nerves in Normal and Denervated Cat Hearts

Abstract: The localization of adrenergic and cholinergic nerves in normal and denervated cat hearts was studied histochemically. The norepinephrine content of atria and ventricles was chemically determined by a spectrofluorometric method. In hearts denervated 9 to 42 days, little or no norepinephrine was detected. Histochemically, many catecholamine-containing fibers were present in the atria and ventricles of normal cats, whereas in denervated cats there were none in one and very few in four. There were many cholinergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…Considerable anatomical evidence exists for the presence of cholinergic receptors in the ventricles (11)(12)(13)(14)(15)(16)(17). Furthermore, acetylcholinesterase activity has…”
Section: Discussionmentioning
confidence: 99%
“…Considerable anatomical evidence exists for the presence of cholinergic receptors in the ventricles (11)(12)(13)(14)(15)(16)(17). Furthermore, acetylcholinesterase activity has…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study is germane to this point: we employed the same degree of pulmonary artery banding in the cat as that used here, but for 60 wk before study (25), an interval greater than that reported to be required for the reinnervation of the hearts of cats (44) or dogs (45) after deliberate surgical cardiac denervation. The heart rate of these cats (25) during anesthesia with 25 mg/kg of ketamine, a phencyclidine derivative with centrally mediated sympathomimetic activity (46), was 181±7 beats/min; for normal control cats in our laboratory after the same anesthesia a similar value of 186±9 beats/min was obtained, but in the identically anesthetized cats with epicardial denervation in the present study, this value was significantly lower at 152±5 beats/min, a value not greatly different from that of 110-140 beats/min which we see in awake, unrestrained cats.…”
Section: Adrenergic Interventionsmentioning
confidence: 99%
“…• Histological studies done since the early 1960s have documented the presence of cholinergic innervation in the ventricular myocardium (1,2). In addition, a number of physiological experiments have demonstrated that stimulation of vagal nerves or administration of cholinergic drugs can depress, although often minimally, the contractile state of the ventricle (3-7).…”
mentioning
confidence: 99%